A case study on the promotional activities practiced by PASDEC Corporation / Mohd Nur Shafiq Sharif - Sharif, Mohd Nur Shafiq (Faculty of Business and Management, 2009)
PASDEC Corporation Sdn Bhd is one of the subsidiaries company under Perbadanan Kemajuan Negeri Pahang (PKNP). The company operated under PKNP at Complex Teruntum, Kuantan. PASDEC Corporation business involved developing residential and commercial building in Pahang state and also developed a few project outside Pahang. For this company, developing quality and satisfactory residential houses is always a first priority. But having only a quality houses and projects is not enough to ensure the smooth and fruitful selling process. In order to get the best results in hand, beautiful houses must be assists with an aggressive and effective marketing communication tools. At present, PASDEC Corp is probably firing with full cylinders. They have done everything from personal to even have their own advertisement, but still the statistics shows that PASDEC sales has slump from 2007 to right until now. So the question to be answer is whether this condition is contributed by the ineffectiveness of PASDEC marketing tools or whether the current unhealthy global economic condition that drawn the plunge of PASDEC overall sales?